Cyber Laundering melalui Online Games: Potensi Ancaman Keamanan Ekonomi - Muchamad Kibar Kaloka; Ika Riswanti Putranti; Sheiffi Puspapertiwi (Journal of International Relations Diponegoro, 2018)
The development of money laundering modus has begun to move into the digital and the internet world, which triggers the emerging of potential of new threats. One of these potentials is the potential threat of cyber laundering through online games. The world of entertainment market, especially in the field of online games that continues to grow has the potential to invite potential money launderers. In Indonesia, this market still does not have a strong regulation. It creates a gap for cyber laundering. This research seeks to see how big the potential threat is and whether the Indonesian government has realized about the potential threat, and how are the chances of the issue to be securitized by the Indonesian government. The research method used is quantitative and qualitative by collecting data and analyzing them to find out how big the potential of the threat and the securitization opportunities of the threat. The result of this research shows that there is a lack of securitization from the Indonesian government due to the related parties in the field of gaming and the government itself has not realized the potential of this threat, so there are gaps that can be entered by potential money launderers.